Molecular and cellular proteomics of fruit maturation in pineapples, ananas comosus var. Comosus - Nor Hidayu Mohd Jamil (2014)
A proteomics approach employing a two dimensional electrophoresis (2-DE) technique with mass spectrometric analyses was performed to separate and identify the proteins from the pineapple fruit at two different stages of ripening. Pineapple (Ananas comosus var. comosus) is a non-climacteric fruit with a unique mode of ripening that is different to climacteric fruits, such as, papaya, banana and tomato. The molecular and cellular mechanism of the fruit remains unclear, particularly during the developmental stages of ripening. As such, this study aims to determine the pineapple fruit proteome and to characterize differentially expressed proteins in two developmental stages i.e mature green (16 weeks) and mature yellow (20 weeks) fruit by peptide mass fingerprinting using LC-QTOF-MS. The comparison of the protein patterns of both stages showed 42 differential expressed protein spots. From this, 32 differentially expressed proteins were identified. Proteins were then classified according to their putative function and known biosynthetic pathways. Functional annotation revealed their involvement in six important biological processes, such as glycolysis and sugar metabolism, stress response and defence, secondary metabolism, protein metabolism, cell structure and protein synthesis. Generally, the pattern of protein expression as well as the putative function of identified proteins argues for a role in major fruits such as tomato, grape, and citrus during physiological developmental and ripening processes. Among the important identified proteins are alcohol dehydrogenase, chalcone synthase, sucrose synthase, heat shock proteins (HSPs), superoxide dismutase and malate dehydrogenase. The potential role of protein differential expression between mature green and mature yellow fruits during ripening is reviewed, and proteomic results also correlate with the known variations of transcripts of the same stages of the fruits. Integration with genomics, transcriptomics, metabolomics and other large scale “-omics” data with systems biology approaches could lead towards the development of new pineapple varieties with enhanced yields, improved nutritional value and to overcome the problem of post-harvest physiological deterioration.